Um projeto colonial chamado abolicionismo : os projetos legislativos para a abolição da escravidão no Brasil e em Portugal (1758-1899) - Gabriel Felipe Silva Bem (2024)
This PhD dissertation aimed to understand the legislative practices of slavery abolition in Brazil and Portugal in an interconnected manner. In addition to comparing the unfolding of the legislative process in these two spaces, we sought above all to highlight its articulation with the discourse that justified the colonialist process in Africa during the 19th century. In this perspective, abolitionism and colonialism are seen as the same process that established new forms of subordination, despite presenting themselves as emancipatory. The main sources of this dissertation were the abolitionist projects and legislation. They were divided into four chronological blocks of analysis focusing on the following contexts: the creation of the first constitutions, debates around the abolition of the slave trade, the process leading to the creation of the "law of free womb", and finally, the laws that promoted the emancipation of the enslaved. Analyzing these sources revealed that abolitionism in Portugal and Brazil, mainly led by political elites, reflected assumptions typical of colonial discourses. These elites understood the enslaved population and their possibilities for the future based on the horizon of expectations created by colonialism. In this way, mechanisms were perpetuated that limited the full freedom of the enslaved population, keeping them in a subordinate position with limitations on rights even after the laws that abolished slavery. Despite these similarities, differences were also noted in the abolitionist process in Brazil and Portugal. In the former, there is a more evident discourse seeking to eliminate populations from Africa from the national space, while in the latter, there was a more apparent attempt to perpetuate forced labor even after the official end of slavery. This difference arose from different historical realities, as in Brazil, the enslaved population was within the national territory, while in Portugal, they were relegated to colonial spaces. However, both were the results of different arrangements based on assumptions of colonial discourses.